teacher participation in the construction of curricular design by competences. Nursing case - UCLA (Revista Electrónica REDINE, 2018)
The paper reports a descriptive study whose objective was to determine the factors associated with teacher participation Nursing Program at UCLA in building competency-based curriculum design. 36 teachers answered a questionnaire with 21 Likert scale items. The results indicated that teachers considered relevant and feasible competency curriculum redesign process. However, they are not motivated to participate and do not have skills and time to attend training activities. It is recommended, to ensure the resources required the participation of teachers in training programs, and, workshops in the curriculum.
Keywords: curriculum design; competitions; teacher involvement